The Effect of Implementation Integrated Management System ISO 9001, ISO 14001, ISO 22000 and ISO 45001 on Indonesian Food Industries Performance - Agus, Purwanto; Ratna Setyowati, Putri; Arman, Hj. Ahmad; Masduki, Asbari; Innocentius, Bernato; Priyono Budi, Santoso; Otta Breman, Sihite (2020)
The purpose of this study was to determine the effect of the implementation of the Integrated Management System (IMAS) particularly the ISO 9001:2015 (Quality), ISO 14001:2015 (Environment), ISO 22000:2018 (Food Safety) and ISO 45001:2018 (Safety) on business Performance of Indonesian Food Industry. The research motivation is due to the inadequate research and works of literature on the impacts of ISO 9001:2015, ISO 14001:2015, ISO 22000:2018 and ISO 45001:2018 on business performance after their implementation in Indonesia. This research was conducted in several food industry companies in Indonesia as many as 426 respondents, who are the employees from 44 food industry companies that have implemented an Integrated Management System in their respective organizations for at least 3 years were recruited using Stratified Random Sampling. Data was collected via electronic questionnaires and analyzed using the Structural Equation Model (SEM) and Linear Structural Model (LISREL) version 8.70. The results of the analyses showed that the implementation of IMAS has significantly influenced the business performance of the selected companies. Interestingly, it is also found that IMAS has contributed to the increase of employee awareness, improvement of the company's image, improvement of quality and safety of the food products, the enlargement of new customers pool and facilitate access to new markets. Moreover, IMAS also has proven an important system that managed to increased customer satisfaction, contributed to the improvement of internal organizational, improve communication culture in the companies, increased employees' productivity as well as reduced the non-compliant products. This research novelty is essential as it outlines a strategic model that could be adapted and adopted by other industries in Indonesia or in other regions in improving their business performance through the implementation of Integrated Management System (IMAS) particularly the ISO 9001: 2015, ISO 22000, ISO 14001 and ISO 45001.